Versions, Revisions and Subversions of the Poetry of Rubén Darío in Century XX - Alemay Bay, Carmen (Anales de Literatura Hispanoamericana, 2008)
This article tries to make a route, from the posmodernismo to end of century XX, of the reception of Rubén Darío in the main Latin American poets. Through analysis of poems dedicated to the teacher of the modernismo, and also of the opinions that in their case these poets have spilled on the author of Azul, we arrived at a series of conclusions of how it has been interpreted the work of Rubén Darío in each one of the poetic stages that compose century XX.